Pengabdian Sebagai Juri dalam Lomba Cerdas Cermat Kimia Se-Sulawesi Utara Dengan Tema Improve and Exspress Your Science with Chemistry - Akbar, Jakub Saddam; Djakariah (Jurnal Pengabdian Masyarakat Isei, 2023)
Abstract Service as a judge in the North Sulawesi Chemistry Quiz Competition is a commitment to advancing and strengthening the quality of education in the field of chemistry in the North Sulawesi region. This competition aims to provide a platform that encourages high school/vocational school students to show their understanding, application and interest in chemistry. As judges, our role is very crucial in assessing participants' knowledge, analysis and problem solving in accordance with the established curriculum. Through a thorough judging process, we will assess the accuracy, depth and clarity of the participants' answers. Emphasis is placed on understanding concepts, analytical skills, as well as practical applications in everyday chemistry. The feedback given to participants is not only intended to assess, but also to provide constructive direction so that participants can continue to improve their understanding of chemistry. The Chemistry Quiz Competition is a forum for creating a healthy competitive atmosphere, encouraging enthusiasm for learning, and improving students' critical and analytical thinking skills. Apart from that, we hope that this competition can foster their interest in chemistry and provide inspiration for the younger generation to explore this field of science further. By contributing as a judge in the North Sulawesi Chemistry Quiz Competition, it is hoped that the next generation will be formed who are knowledgeable, have strong skills in chemistry, and have the enthusiasm to continue learning and developing, which will ultimately contribute to the progress of science and technology. society in the future. Abstrak Pengabdian sebagai juri dalam Lomba Cerdas Cermat Kimia Se-Sulawesi Utara merupakan komitmen untuk memajukan dan memperkuat kualitas pendidikan di bidang kimia di wilayah Sulawesi Utara. Lomba ini bertujuan untuk memberikan platform yang memacu para pelajar SMA/SMK untuk menunjukkan pemahaman, penerapan, dan ketertarikan mereka terhadap ilmu kimia. Sebagai juri, peran kami sangat krusial dalam menilai pengetahuan, analisis, serta pemecahan masalah peserta sesuai dengan kurikulum yang telah ditetapkan. Melalui proses penjurian yang teliti, kami akan menilai keakuratan, kedalaman, dan kejelasan jawaban para peserta. Penekanan diberikan pada pemahaman konsep, kemampuan analisis, serta aplikasi praktis dalam kimia sehari-hari. Feedback yang diberikan kepada peserta tidak hanya bertujuan untuk menilai, tetapi juga untuk memberikan arahan yang konstruktif agar peserta dapat terus meningkatkan pemahaman mereka terhadap kimia. Lomba cerdas cermat kimia menjadi wadah untuk menciptakan suasana kompetitif yang sehat, mendorong semangat belajar, serta meningkatkan keterampilan berpikir kritis dan analitis para pelajar. Di samping itu, kami berharap lomba ini dapat memupuk minat mereka terhadap ilmu kimia serta memberikan inspirasi bagi generasi muda untuk mengeksplorasi bidang ilmu ini lebih lanjut. Dengan kontribusi sebagai juri dalam lomba cerdas cermat kimia Se-Sulawesi Utara, diharapkan dapat terbentuknya generasi penerus yang berpengetahuan luas, memiliki keterampilan yang kuat dalam ilmu kimia, serta memiliki semangat untuk terus belajar dan berkembang, yang pada akhirnya akan berkontribusi pada kemajuan ilmu pengetahuan dan masyarakat di masa depan.